Vascular flora from Villa María and Amancaes Lomas, Lima, Peru - Trinidad, Huber (2012)
This paper reports the inventory of vascular flora of Villa Maria and Amancaes Lomas, Lima, Peru. The expeditions for inventorying both locations were conducted in September and October 2011. We registered 121 species in both localities, belonging to 99 genera and 41 families. The most diverse families were Asteraceae and Boraginaceae with 17 and 8 species respectively. Villa Maria lomas 112 species in 99 genera and 39 families were registered, of which 20 are endemic. Villa Maria lomas is one of the most diverse lomas in Lima after Lachay and Carabayllo. In Amancaes lomas, 51 species in 43 genera and 28 families were registered, of which 9 are endemic. The low number of species in Amancaes lomas is due to the reduction of the area occupied, caused by urban growth. In both localities, the vegetation is predominantly herbaceous, with 77% of the species in Villa Maria and 86% in Amancaes. Both lomas are having a high impact by the urban expansion, which has reduced their area size and contributed to their pollution, mainly with solid waste.